Method of dynamic real-time authentication - Chuan-wu MAO; Yang CHENG; Wen-ming YU (网络与信息安全学报)
To solve the problem organization’s insider threats which was brought by internal staff through identity spoofing. A method of dynamic real-time authentication was presented. By faking exceptions of mouse to build dynamic authentication, when continuously consecutive authentication were abnormal, user was forced into fixed scene certification which was building of memory game. An identity verification experiment, in which 15 participants were involved, showed that the performance of proposed method was encouraging with FAR of 1.8% and FRR of 3.0% and authentication time of 8.12 s for authentication. The experiment shows that the method is not only real-time but also has a better user experience and accuracy.